Perlindungan Hukum Bagi Korban Hubungan Seksual Sedarah (Studi Pada Unit Perlindungan Perempuan Dan Anak SATReskrim Polrestabes Medan) - Dhoory Vinevera Sigiro; Suhaidi Suhaidi; Ibnu Affan (Mahesa Research Center, 2020)
This research is a normative juridical study supported by empirical juridical research. This research is analytical descriptive, that is, describing an object or event without an intention to draw conclusions that are generally accepted. The data source of this research consists of primary data and secondary data, in the form of primary, secondary and tertiary legal materials. The analysis used in this study is qualitative data analysis. Based on the research results obtained, the regulation of incest in a variety of laws currently in force still emphasizes the form of incest committed by a child. Whereas incest is based on the agreement of both parties for those who are adults has not been specifically regulated. The role of the Satreskrim Polrestabes Medan women's and child protection unit in providing legal protection for victims of incest, by seeking the rights of victims. Obstacles to the Protection Unit of Women and Children of the Satreskrim Medan District Police in terms of legal handling of incest in the case of sexual intercourse in the absence of synergic relations between the existing institutions.